2007
DOI: 10.2135/cropsci2006.07.0495
|View full text |Cite
|
Sign up to set email alerts
|

A Large‐Effect QTL for Grain Yield under Reproductive‐Stage Drought Stress in Upland Rice

Abstract: Genetic control of yield under reproductive‐stage drought stress was studied in a population of 436 random F3–derived lines from a cross between the upland rice (Oryza sativa L.) cultivars Vandana and Way Rarem. Screening was conducted under upland conditions at IRRI during the dry seasons of 2005 and 2006. Lines were evaluated in drought stress and nonstress trials in both years to identify QTL contributing to drought resistance. For QTL detection, a set of random lines and the highest and lowest‐yielding lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
414
5
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(458 citation statements)
references
References 45 publications
36
414
5
3
Order By: Relevance
“…However, very few QTLs are actively targeted in breeding programs because most QTLs have not been validated in different genetic backgrounds and environments (Price et al 2002b;Yue et al 2008), which may also have hampered the pace of DT breeding. Nevertheless, several major DT QTLs, such as qDTY 12.1 (Bernier et al 2007;Mishra et al 2013), qDTY 1.1 (Vikram et al 2011), qDTY 6.1 (Venuprasad et al 2012), and the QTL closely associated with the markers EM11-11 ) and RM410 (Gu et al 2012) have been identified and used for developing DT varieties via MAS. Through functional and comparative genomic studies, many stressresponsive transcription factors were recently shown to affect DT (Liu et al 2007;Lu et al 2009;Ye et al2009;Zhao et al 2010;Jeong et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, very few QTLs are actively targeted in breeding programs because most QTLs have not been validated in different genetic backgrounds and environments (Price et al 2002b;Yue et al 2008), which may also have hampered the pace of DT breeding. Nevertheless, several major DT QTLs, such as qDTY 12.1 (Bernier et al 2007;Mishra et al 2013), qDTY 1.1 (Vikram et al 2011), qDTY 6.1 (Venuprasad et al 2012), and the QTL closely associated with the markers EM11-11 ) and RM410 (Gu et al 2012) have been identified and used for developing DT varieties via MAS. Through functional and comparative genomic studies, many stressresponsive transcription factors were recently shown to affect DT (Liu et al 2007;Lu et al 2009;Ye et al2009;Zhao et al 2010;Jeong et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bernier et al (2007) identified large-effect QTLs for grain yield under drought stress. If confirmed, these identified QTLs have to be fine mapped for use in breeding programs.…”
Section: Qtl For Yield and Yield Related-traits Under Droughtmentioning
confidence: 99%
“…A recombinant inbred population obtained from a cross between high-yielding lowland rice IR64 and Cabacu was used to identify 10 QTLs for grain yield and component traits under reproductive-stage drought stress (Trijatmiko et al, 2014). The qDTY12.1 is the first reported large-effect QTL for grain yield under severe upland reproductivestage drought conditions and was identified in a population of 436 F3-derived lines from a cross between Vandana and Way Rarem (Bernier et al, 2007). Two other large-effect QTLs, qDTY2.1 and qDTY3.1, well known to affect grain yield under lowland reproductivestage drought, were identified in a back cross inbred line (BIL) population derived from a cross between Swarna and Apo.…”
Section: Qtl For Yield and Yield Related-traits Under Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies at the IRRI (International Rice Research Institute) found that there is moderate to high heritability of grain yield under drought stress [4,6,7]. Basically, the main objectives of a breeding program for drought tolerant rice are to determine standard tolerant varieties, to identify important traits, and to evaluate the tolerant levels at seedling and reproductive stages.…”
Section: Introductionmentioning
confidence: 99%